A Implementasi Ekonomi Syari'ah : Marketing Syari'ah: PENGARUH PELABELAN HALAL PADA PRODUK KOSMETIK HALAL WARDAH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM DI KABUPATEN KENDAL - Muslih, Imam (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2025)
As a Muslim, it is obligatory to always consume halal products, including cosmetics. This study aims to determine the effect of halal labeling as an independent variable in this study on the purchase decision of Wardah cosmetics, which is the dependent variable. The data collection method was carried out through a questionnaire. The population in this study were Muslim consumers who had purchased and used Wardah cosmetics in the city of Kendal. The sample required was 103 respondents using purposive sampling. This study used multiple linear regression analysis techniques and data testing using the SPSS Statistics 25 program. The results of this study indicate that halal labeling has a positive and significant effect on the purchase decision of Wardah cosmetics, both partially and simultaneously. The influence of the five variables is very strong, indicated by the coefficient of determination of 78%.